Survey of infection control and antimicrobial stewardship practices in Australian residential aged‐care facilities. Issue 5 (May 2015) - Stuart, R. L.; Marshall, C.; Orr, E.; Bennett, N.; Athan, E.; Friedman, D.; Reilly, M.; Members of RACRIG (Residential Aged Care Research Interest Group)
Abstract This study assessed infection prevention and antimicrobial stewardship (AMS) practices in Australian residential aged‐care facilities (RACF). Two hundred and sixty‐five surveys (15.6%) were completed with all states represented and the majority (177 (67.3%)) privately run. Only 30.6% RACF had infection control trained staff on site. Few facilities had AMS policies, only 14% had antimicrobial prescribing restrictions. Most facilities offered vaccination to residents (influenza vaccination rates >75% in 73% of facilities), but pneumococcal vaccination was poor.